Ben Jonson : a life - Donaldson, Ian, 1935- (Oxford University Press, 2011)
Ben Jonson was the greatest of Shakespeare's contemporaries. His fame rests not only on the numerous plays he had written, but on his achievements over three decades as principal masque writer to the early Stuart court, where he had worked in creative, if at times stormy, collaboration with Inigo Jones. One of the most accomplished poets of the age, he was, in fact if not in title, the first Poet Laureate in England. This biography draws on freshly discovered writings by and about Ben Jonson, and locates his work within the social and intellectual contexts of his time, and it depicts a life full of drama. Jonson's early satirical play, The Isle of Dogs, landed him in prison, and brought all theatrical activity in London to a temporary, and very nearly permanent, standstill. He was "almost at the gallows" for killing a fellow actor after a quarrel, and converted to Catholicism while awaiting execution. He supped with the Gunpowder Conspirators on the eve of their planned coup at Westminster. After satirizing the Scots in Eastward Ho! he was imprisoned again, and throughout his career was repeatedly interrogated about plays and poems thought to contain seditious or slanderous material. Throughout this biography, the auithor provides the fullest picture available of Jonson's personal, political, spiritual, and intellectual interests, and he discusses all of Jonson's major poetry and drama, plus some newly discovered works. Jonson emerges from this study as a more complex and volatile character than previously depicted, and as a writer whose work strikingly foresees the modern age.